Editorial (English) - Mota, Maurício (Revista de Direito da Cidade, 2016)
DOI: 10.12957/rdc.2016.26354 JOURNAL OF CITY LAW Editorial for vol. 08-4 (2016) The Journal of City Law, classified by MEC / CAPES as Qualis A1, Law and registered in the Web of Science, is pleased to inform all its readers that the Qualis Law Commission, in October 2016, confirmed the qualification of the Journal as Qualis A1, Law. This is excellent news, which comes to crown the work of all the organizers of the Journal, encouraging us, more and more, to produce a better and better journal (...).